Researching a Posthuman World Interviews with Digital Objects - Adams, Catherine; Thompson, Terrie Lynn.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book provides a practical approach for applying posthumanist insights to qualitative research inquiry. Adams and Thompson invite readers to embrace their inner - and outer - cyborg as they consider how today's professional practices and everyday ways of being are increasingly intertwined with digital technologies. Drawing on posthuman scholarship, the authors offer eight heuristics for "interviewing objects" in an effort to reveal the unique - and sometimes contradictory - contributions the digital is making to work, learning and living. The heuristics are drawn from Actor Network Theory, phenomenology, postphenomenology, critical media studies and related sociomaterial approaches. This text offers a theoretically informed yet practical approach for asking critical questions of digital and non-digital things in professional and personal spaces, and ultimately, for considering the ethical and political implications of a technology mediated world. A thought-provoking and innovative study, this book will be of great interest to scholars and researchers of technology studies, digital learning, and sociology.
Keywords: Sociology-Research.; Ethnography; Educational technology; Humanities-Digital libraries